(3ocfGT ajg ehTMGJ hfbhd COHjIs
(3ChdgG (B:s
(3NP Edjc GdYde jG QLd aSjCJj HYOg GdYeod s
(3BNQgG (B:s
(3bGd hgd jMSOfG bdJ fYe Efg Gdadob s
(3ajg fbhd dZhjI hJGQjNjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B156 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs